Respuesta :

Answer:

(-1,3)

Step-by-step explanation:

Graph the given system of equations

y=-x+2  

make a table for each equation to graph it

Lets assume some value for  x  and find out y

x     y=-x+2

-1      -(-1) + 2= 3

0       0+2 = 2

1         -1+2 = 1

Now make  a table for second equation

y= 4x+7

Lets assume some value for  x  and find out y

x     y= 4x+7

-1       4(-1) +  7= 3

0       4(0) + 7 = 7

1        4(1) + 7 = 11

The graph is attached below

Solution is (-1,3)


Ver imagen lisboa